Association between Sleep Disruption and Levels of Lipids in Caucasians with Type 2 Diabetes - Wan Aizad Wan Mahmood; Mohd Shazli Draman Yusoff; Lucy Ann Behan; Andrea Di Perna; Tommy Kyaw Tun; John McDermott; Seamus Sreenan (International Journal of Endocrinology)
Aim. To investigate the association between sleep quality and duration with lipid and glycaemic control in Caucasian subjects with type 2 diabetes. Methods. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) in 114 type 2 diabetes (T2DM) subjects. Comparisons were made between subjects with different sleep quality and sleep duration. Hierarchical multiple regression analyses were used to determine contributors to metabolic parameters. Results. Subjects with poor sleep quality (PQ; PSQI ≥ 6) had higher systolic blood pressure, glycated haemoglobin, urine albumin : creatinine ratio (UAC), total cholesterol (TC), and triglycerides (TG) ( for all) compared to those with good sleep quality (GQ; PSQI ≤ 5). Long sleep duration (LSD) subjects had higher TC and short sleep duration (SSD) subjects had higher TG compared to those with medium sleep duration. Sleep duration and PSQI score were independent predictors of TC and low-density lipoprotein cholesterol (LDL), contributing to 14.0% and 6.1% of the total variance, respectively. Conclusions. In this Caucasian T2DM population, PQ is associated with adverse cardiovascular risk markers, and long and short sleep disruptions have an independent negative impact on lipids. Sleep assessment should be included as part of a diabetes clinic review.